HYPOTHESES TESTING ON INFLUENCE OF TOURISM APPS TOWARDS TOURIST TRAVEL NEEDS AND TOURISM ATTRACTION - Qistina Donna, Lee Abdullah; Aimuni Athirah, Latif; Norsyahbany, Mansor (2021)
o develop interesting tourism apps, tourists’ travel needs must be found out in order tolink it with the features of the application. Needs is something necessary to the tourist while they are travelling in order to satisfy their own wants. Tourists’ traveling needs based on their own preference and way of life. However, there are also tourists that have needs based on the locations to visit, the different locations give different needs to the tourists. The detailed travel information available on tourism Apps helps to minimize the tourists’ efforts and costs in planning their trips. Tourism Apps provide tourists with various choices and suggestions of affordable travelling activities, as there are numerous discounts and proposalfrom various travel agencies and hotels that can be immediately found in there. This paper focuses on the hypotheses testing on influence of tourism apps towards tourist and tourism attraction. The finding of paper also can prove the influence of tourism apps towards tourism industry in aspects of developing new prototype of tourism apps based on tourist needs. It is to testing hypotheses of the influence of tourism apps towards travel needs and tourism attractions. This paper will introduce the best features to be including in tourism apps.